The Causes and Impact of Public Elementary School Regrouping - Mariyadi; Slamet Subiyantoro; Sukarno (Jurnal Ilmiah Sekolah Dasar, 2023)
Regrouping can solve the problem of a need for more students and teachers in schools, but this also needs to improve its implementation. This study aims to analyze the factors that cause public elementary school regrouping and explain the impact of implementing school regrouping policies. This research uses a qualitative method with a case study type. The subjects of this study were 37 public elementary schools (SDN). Data collection techniques were carried out in this study through interviews, observation, and documentation. The data validity technique used in this study was method triangulation and key informant review. Data analysis techniques using interactive models include data reduction, data presentation, and conclusion. The results showed that the main factor causing school regrouping was the low number of students and teachers. The impact of school regrouping includes overcoming the problem of the shortage of students and teachers, the occurrence of effectiveness and efficiency in school administration, etc. In addition to the positive impacts, school regrouping also has negative impacts, namely the emergence of disappointment among teachers who are forced to change assignments and adapt themselves to a new work or school environment, non-fulfillment of teaching hours for honorary teachers, adjustments to character and work culture, etc. The results of this study can contribute to the better implementation of school regrouping.